Analysis On Application Of Biochar Composites In Removal Of Hexavalent Chromium From Wastewater - Ang, Zi Ying (2020)
Cr(VI) contamination in wastewater is an important environmental issue to be considered with human health concern. Currently, biochar as a green and sustainable organic matter are frequently studied on its application to environmental remediation especially wastewater treatment. Experiments were conducted on biochar composites that were incorporated with various active components to improve the performance of pristine biochar. In the present study, performances of several biochar composites on Cr(VI) removal from aqueous solution were evaluated with the analysis of multiple journals. The foreign materials available for synthesis of biochar composites were categorized as carbonaceous material, nano-zerovalent iron (nZVI), metal/ metal oxide nanoparticles and polymer. Biochar composites were synthesised by either preor post-pyrolysis of pristine biochar treated with respective active components. The results of characterization techniques included Electron Microscope, Multipoint N2-BET Adsorption Method, Fourier Transform Infrared Spectroscopy (FTIR) and X-Ray Diffraction (XRD) of biochar composites were discussed and analysed. Results showed the successful attachment of the active components on pristine biochar with the presence of additional functional groups or the foreign materials observed on biochar surface. The mechanisms and kinetics models related to Cr(VI) removal were also discussed. Incorporation of foreign components enhanced the removal of Cr(VI) with additional surface functional groups or elements in biochar composites to react with Cr(VI). In the view of the kinetics data, pseudo-second order kinetic and Langmuir isotherm showed higher level of correlation coefficients (R2 ) where they were best fitted to describe Cr(VI) adsorption, indicated that monolayer chemisorption of Cr(VI) on homogeneous distributed active sites were significant. Based on the results of parameter study, adsorption, reduction and precipitation processes for enhanced Cr(VI) removal were affected by pH, residence time, initial Cr concentration and adsorbent dosage while pH of solution possessed greater impact on adsorption of Cr(VI). PEI/ biochar composite showed highest maximum adsorption capacity at pH 6.8 with adsorbent dosage of 1g/L and initial Cr(VI) concentration of 100 mg/L.